Associations Between an Overall, Healthful and Unhealthful Low-Fat Dietary Patterns and Breast Cancer Risk in a Mediterranean Cohort: The SUN Project. (7th June 2021) - Buenosvinos, Inmaculada Aguilera; Martinez-Gonzalez, Miguel Ángel; Gea, Alfredo; Zazpe, Iztiar; Lázaro, Cesar Ignacio Fernández; -Bayona, Rodrigo Sánchez; Toledo, Estefania
Abstract: Objectives: Dietary patterns may have a greater influence on human health than individual foods or nutrients and they are also being widely studied in the field of breast cancer prevention. Beyond the adequate balance of macronutrients, evidence shows that the quality of fat sources may play an important role in health outcomes. Our aim was to assess the relationship between healthful and less healthful low-fat dietary patterns in relation to breast cancer in a Mediterranean cohort (the SUN project). Methods: The SUN Project is a Mediterranean dynamic prospective follow-up cohort study assessing participants every 2 years. We evaluated 10, 930 middle-aged women initially free of breast cancer during a median of follow-up of 12.1 years. Dietary variables were evaluated through a previously validated 136-item FFQ. We calculated an overall, an unhealthful, and a healthful low-fat-diet score (rang: 0–30 points) based on the percentage of energy from total and subtypes of carbohydrate, fat, and protein. Participants were then categorized into tertiles.  Incident breast cancer was de primary outcome. We fitted Cox regression models adjusted for potential confounders to investigate the relationship between baseline categories of low-fat-diet scores and the incidence of breast cancer- overall and stratified by menopausal status-. Results: During 123, 297 person-years of follow-up, 119 cases of incident breast cancer were confirmed. Among postmenopausal women, a significant direct association with postmenopausal breast cancer (comparing tertile 2 vs. tertile 1, HR = 2.60; 95% CI 1.24–5.45, P value = 0.012) was found.  None of the other associations was statistically significant. Conclusions: In this Mediterranean prospective cohort study, a moderate adherence to an unhealthy low-fat-diet-score might increase the risk of postmenopausal breast cancer. These results must be further confirmed in future studies. Funding Sources: The SUN project received funding from the Spanish Government-Instituto de Salud Carlos III, and the European Regional Development Fund, the Navarra Regional Government and the University of Navarra.